Perpetuating the Cycle: The Failure of APHIS and EPA to Consider the Cumulative Impact of Pairing Herbicides with Herbicide-Resistant Crops - Mahoney, Michael (Columbia Journal of Environmental Law, 2019)
Under the existing statutory framework, the U.S. Department of Agriculture’s Animal and Plant Health Inspection Service (“APHIS”) has the authority to regulate certain genetically engineered crops, while the Environmental Protection Agency (“EPA”) regulates all herbicide products sold in the United States. Although the development of a crop engineered to be resistant to a certain herbicide contemplates the future widespread use of that herbicide, EPA and APHIS fail to account for this cumulative impact. Specifically, when performing a National Environmental Policy Act (“NEPA”) analysis for the deregulation of crops designed to be herbicide-resistant, APHIS violates NEPA and its implementing regulations by failing to analyze the environmental effects of the increased herbicide use that the deregulation presupposes. Meanwhile, the courts have determined that EPA need not comply with NEPA when registering herbicides, finding the Federal Insecticide, Fungicide, and Rodenticide Act (“FIFRA”) analysis sufficient even though it does not evaluate the environmental effects of registering the herbicide. Consequently, APHIS, EPA, and the courts have perpetuated a cycle of herbicide registration and herbicide-resistant crop deregulation in which neither EPA nor APHIS fully contemplates the cumulative impact of their respective actions. ... The regulation of the herbicide 2,4-Dichlorophenoxyacetic acid (“2,4-D”); the deregulation of Enlist™ corn and soybean, designed to be resistant to 2,4-D and glyphosate; and the regulation Enlist Duo™, designed for use in controlling weeds in corn and soybeans genetically-engineered to tolerate 2,4-D and glyphosate, is emblematic of the cycle that this regulatory regime continues. ... This article will proceed as follows. Part II will address the cycle of herbicide use that the introduction of herbicide-resistant crops perpetuates, with particular focus on the Enlist™ varieties and 2,4-D. Part III will explain the regulatory system for herbicides and herbicide-resistant crops and will share some common criticisms of that regime. Part IV will outline the parts of NEPA and its implementing regulations pertinent to herbicide registration and the deregulation of herbicide-resistant crops. Part V will establish that APHIS failed to consider the impact of the increased herbicide use contemplated by its decision to deregulate the Enlist™ varieties, thus violating NEPA. Part VI will demonstrate that EPA’s decisions to reregister 2,4-D and register Enlist Duo™ did not account for the effects of registering these herbicides for use with herbicide-resistant crops. Part VII will demonstrate that EPA and APHIS consistently fail to consider the cumulative impact of pairing herbicides with herbicide-resistant crops. Part VIII will recommend that the power to regulate both herbicides and herbicide-resistant crops reside in APHIS.